UnB's Degree in Education for Rural Areas (LEdoC - UnB) and the training of teachers/collective intellectuals: influences of Socialist Pedagogy in the training of educators for rural areas based in the Kalunga Territory - Goiás - Mônica Castagna Molina; Pedro Henrique Xavier; Marcelo Fabiano Rodrigues Pereira (Universidade Federal do Norte do Tocantins, 2022)
The present text discusses the Degree in Education for Rural Areas at the University of Brasília, seeking to identify which elements of the training process of this Degree contribute to the formation of the Kalunga Quilombo people as collective intellectuals and to their performance as teachers, school and community managers, so as to incorporate the knowledge of these individuals and their demands in this process. The methodology is based on Dialectical Historical Materialism and research carried out both at LEdoC-UnB and in the Kalunga-Goias Quilombola territory. These researchs are linked to the work supported by CNPq and to Doctoral research, in both, resorting to the instruments of participant research (Schmidt, 2006), making observations, document analysis of academic productions of the individuals involved and semi-structured interviews. This article is based on the theoretical and practical construct of Education for Rural Areas; the influences of Socialist Pedagogy and the formation of collective intellectuals in the Gramscian perspective. The outcomes indicate that the formation of LEdoC-UnB has had repercussions on both teacher's training and individuals' social spheres of action, such as school and community leaders strengthening processes that have been triggering relevant collective transformations, even before tensions and contradictions that permanently challenge their performance.